Successful Sargassum bed formation in a “Isoyake” area by net transplantation of juveniles with small algae - Mukai, Yukinori; Koyama, Yoshiaki; Shiba, Shuici; Tanihuzi, Naozumi; Iguchi, Hisakazu; Matsuda, Kiyoshi; Uta, Kunio (Maruzen Co Ltd, 2003)
Transplanted juveniles of the Sargassum spp were used to try to create Sargassum beds in the "Isoyake" Area of Nasa Bay in Tokushima Prefecture between 1996-2001. There were no juveniles of the next generation in the area until 1997 because of the high population of grazing herbivores. From 1998, a different method of transplantation, involving young Sargassum and other small annual and perennial algae was used. Moreover, two types of protective netting were settled over the transplanted area to prevent grazing by herbivores. One type net was a roofless cage net that was used from 1997, the other type was a cover net that was used from 1999. Consequently, Sargassum juveniles appeared among the small annual and perennial algae on the substratum of the sea bottom. This fact indicated that the existence of small algae protected the young Sargassum algae from grazing by herbivores. Thereafter, Sargassum beds regenerated and spread throughout the adjacent area. The new method employed in this study, combining the transplantation of small algae with Sargassum and setting protective netting to prevent by grazing herbivores were effective in the production of Sargassum bed formation in the "Isoyake" Area.